If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 13 = -71 + -9x Reorder the terms: 13 + 3x = -71 + -9x Solving 13 + 3x = -71 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 13 + 3x + 9x = -71 + -9x + 9x Combine like terms: 3x + 9x = 12x 13 + 12x = -71 + -9x + 9x Combine like terms: -9x + 9x = 0 13 + 12x = -71 + 0 13 + 12x = -71 Add '-13' to each side of the equation. 13 + -13 + 12x = -71 + -13 Combine like terms: 13 + -13 = 0 0 + 12x = -71 + -13 12x = -71 + -13 Combine like terms: -71 + -13 = -84 12x = -84 Divide each side by '12'. x = -7 Simplifying x = -7
| -7x+7y=7 | | -7-x=-5 | | -67-2x=5-10x | | 94-2x=6x+6 | | 14-7x=82-21x | | 4x+3(12x-7)= | | 2(x)+90= | | 17x-13=32+48 | | -37-3x=5-10x | | 99-4x=9x+21 | | 55-2x=5-10x | | 15x+2= | | 7y-18=17 | | -11-7x=10x+23 | | -6x+2y=-2 | | 4x+10=110-6x | | 4x+14=-63-7x | | 11x+9=7x+29 | | 49k^2-16=0 | | g^2+4g=21 | | 134-5x=5x+14 | | x^4+x=0 | | 10x+5y=27 | | 3x+13=73-3x | | 4x-3=13x-48 | | 5b-3-10b-4= | | g+4g=21 | | 2+12x=90+x | | 5x-1=12x-22 | | 230-4x=41x+20 | | 3x^3+12x^2=0 | | 3(3g+2)=10.5 |